Wave diffraction and radiation by a vertical circular cylinder standing in a three-dimensional polynya - Ren, K; Wu, GX; Ji, C (Elsevier, 2018)
The wave diffraction and radiation problem of a body in a polynya surrounded by an ice sheet extending to infinity is considered through a vertical circular cylinder. The ice sheet is modelled through the elastic thin-plate theory and the fluid flow through the linearized velocity potential theory. In particular, when the polynya is of the circular shape, eigenfunction expansion method is applied to the two regions below the ice sheet and the free surface respectively, and the velocity and pressure continuity conditions are imposed on the interface of the two regions. The wave motion in the polynya, the hydrodynamic coefficients as well as the exciting forces on a body located arbitrarily in the polynya are calculated. The nature of highly oscillatory behaviour of the results is investigated and their physical implications are discussed.